Utilization of an ionic liquid/urea mixture as a physical coupling agent for agarose/talc composite films - Shamsuri, Ahmad Adlie; Daik, Rusli (MDPI, 2013)
An ionic liquid, 1-n-butyl-3-methylimidazolium chloride (BmimCl) was blended with urea at 1:1 mole ratio to create a BmimCl/Urea mixture. The agarose/talc composite films containing the BmimCl/Urea mixture were then acquired through a gelation method. The weight ratio of agarose and talc was fixed at 4:1, while the content of BmimCl/Urea was varied from 0 to 10 wt % relative to the overall weight of the composite films. The tensile stress and modulus results showed the optimum BmimCl/Urea content in the composite film lies at 8 wt %. The talc particles are embedded in the agarose matrix and there are no pullouts for the composite films containing BmimCl/Urea as demonstrated by SEM micrographs. The addition of BmimCl/Urea increased the glass transition temperature of the composite films, however, the thermal decomposition temperature decreased drastically. FTIR and FT-Raman spectra indicated the existence of interaction between agarose and talc, which improves their interfacial adhesion. As a conclusion, a BmimCl/Urea mixture can be utilized as a coupling agent for agarose/talc composite films.